Islamic Fintech in Indonesia: Between Innovation and Sharia Compliance - Said, Muh. Sa’ad; J, Jumriani; Sapa, Nasrullah bin; H, Darmawati (Media Hukum Indonesia (MHI), 2026)
Sharia Fintech represents a digital financial innovation that integrates technology with Islamic principles such as the prohibition of riba (usury), gharar (uncertainty), and maysir (gambling). This study analyzes the legal framework and Sharia compliance of fintech in Indonesia through a juridical-normative approach to OJK (Financial Services Authority) regulations and DSN-MUI (National Sharia Council–Indonesian Ulema Council) fatwas. The findings indicate that the application of Maqashid al-Shariah, particularly Hifz al-Mal (protection of wealth) and Hifz al-Din (protection of religion), serves as a crucial foundation for the development of fair and sustainable Sharia fintech. Although regulations such as OJK Regulations No. 3 and No. 26 of 2024, along with DSN-MUI Fatwa No. 117, have provided essential guidelines, there remains a gap between the ideality of fatwas and digital practices—especially in the implementation of the Murabahah contract. Therefore, institutional synergy and the strengthening of technology-based Sharia compliance governance are required to ensure a balance between innovation and Islamic principles.